Faktor Penyebab Rendahnya Jumlah Pria Menjadi Akseptor Keluarga Berencana - I Dewa Ayu Ketut Surinati (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2015)
The main purpose of this study is to describe factors that causes a low number of men as Family planning acceptor. The research methods that used in this study is consecutive sampling and for the approach used the cross sectional mode by using sample counted 123 responden. Analysis of the data by discirftiv. The results of this Of all existing factors that cause a low number of men that used family planning, the highest percentage was the knowledge factor which the number of the male respondents that had bad knowledge of family planning are 72 persons (58,55%).